The Determinants Analysis of Exchange Rate Volatility of Rupiah Towards Indonesian Oil and Gas Import - Palladjarang, Ismail Kadir H; Paddu, Abd Hamid; Reviane, Indraswati Tri Abdi (PT. Maju Malaqbi Makkarana, 2023)
This study aims to analyze the determinants of rupiah exchange rate volatility and its impact on Indonesia's oil and gas imports. The variables observed in this study are economic growth, interest rates, inflation, rupiah exchange rate volatility and Indonesia's oil and gas imports. All data used in this study are secondary data obtained from 2005 to 2019 time series recordings obtained from the Central Bureau of Statistics, Investing.com and Bank Indonesia. Data were analyzed using the two-stage least squares (2SLS) method in the IBM SPSS Statistics application 23. Based on the analysis results, economic growth was found to have a positive effect and interest rates had a positive effect. negative and significant impact on oil and gas imports due to fluctuations in the rupee exchange rate. Although inflation is negatively correlated, there is no significant impact on oil and gas imports through fluctuations in the rupee exchange rate.